Endothelin Type A Receptor Antibodies Are Associated With Angiotensin II Type 1 Receptor Antibodies, Vascular Inflammation, and Decline in Renal Function in Pediatric Kidney Transplantation - Pearl, Meghan H. (Kidney Int Rep, 2020)
INTRODUCTION: Autoantibody to angiotensin II type 1 receptor (AT1R-Ab) has been recognized as a non-human leukocyte antigen (HLA) antibody relevant in transplantation. Endothelin type A receptor antibody (ETAR-Ab) has been strongly associated with AT1R-Ab, but the data in kidney transplantation are scarce. METHODS: We examined the relationship of ETAR-Ab and AT1R-Ab with clinical outcomes, biopsy findings, inflammatory cytokines, and HLA donor-specific antibody (DSA) in a cohort of pediatric renal transplant recipients. Sixty-five patients were longitudinally monitored for ETAR-Ab, AT1R-Ab, HLA DSA, interleukin (IL)-8, tumor necrosis factor-α, IL-1β, interferon-γ, IL-17, IL-6, renal dysfunction, hypertension, rejection, and allograft loss during the first 2 years post-transplant. RESULTS: Fifteen patients (23%) had AT1R-Ab alone, 1 (2%) had ETAR-Ab alone, 23 (35%) had both ETAR-Ab and AT1R-Ab, and 26 (40%) were negative for both antibodies at all timepoints. Having both ETAR-Ab and AT1R-Ab was associated with >30% decline in estimated glomerular filtration rate (P = 0.024), arteritis (P = 0.016), and elevated IL-8 levels (P = 0.010), but not rejection, HLA DSA, or allograft loss. Having both antibodies resulted in greater increases in IL-8 compared with AT1R-Ab alone, even when controlled for additional clinical factors, including HLA DSA (P = 0.012). CONCLUSION: Our study demonstrates that, in pediatric kidney transplantation, ETAR-Ab is highly associated with AT1R-Ab, but there are a subset of patients with AT1R-Ab alone. Having both antibodies is significantly associated with arteritis, elevated IL-8, and decline in renal function, and our results suggest possible interaction effects. Better understanding of this interaction may be informative in developing protocols for testing, treatment, and prevention of allograft injury.